2015
DOI: 10.1093/ndt/gfu399
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal and patient outcomes in anti-GBM disease: clinicopathologic analysis of a two-centre cohort

Abstract: Oligoanuria is the strongest predictor of patient and renal survival while percentage of glomerular crescents is the only pathologic parameter associated with poor renal outcome in anti-GBM disease. Kidney biopsy may not be necessary in oligoanuric patients without pulmonary haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 25 publications
8
81
3
5
Order By: Relevance
“…This was in a native kidney and was not associated with a positive ANCA result. Anti-GBM disease is classically a monophasic illness; although relapses can occur (20), they are often in the context of coexistent ANCA positivity (21,22). As seen in previous studies, we found that double-positive cases tended to be older (10,21,23).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was in a native kidney and was not associated with a positive ANCA result. Anti-GBM disease is classically a monophasic illness; although relapses can occur (20), they are often in the context of coexistent ANCA positivity (21,22). As seen in previous studies, we found that double-positive cases tended to be older (10,21,23).…”
Section: Discussionsupporting
confidence: 82%
“…Anti-GBM disease is classically a monophasic illness; although relapses can occur (20), they are often in the context of coexistent ANCA positivity (21,22). As seen in previous studies, we found that double-positive cases tended to be older (10,21,23). A diagnosis of "true" anti-GBM disease can be particularly challenging in this group because older patients may be less likely to undergo renal biopsy.…”
Section: Discussionsupporting
confidence: 75%
“…Other reports have described similarly low levels of renal recovery in patients presenting with dialysis-dependent kidney failure, with the highest rate of approximately 20% recovery in one series (66). Predictors of poor renal outcome include severity of renal dysfunction at presentation, the proportion of glomeruli affected by crescents, and oligoanuria at presentation (17,18,74). In the Hammersmith series, no patient who required hemodialysis and had 100% crescents on kidney biopsy recovered renal function, and so withholding treatment (and its incumbent toxicity) is often considered in these cases.…”
Section: Outcome and Prognosismentioning
confidence: 82%
“…Whether these findings hold true for European patients is less clear. In a recent study of 43 patients with GS referred to two departments in England over a 20-years period, 1-year patient survival was associated with the presence of multiple co-morbidities, ANCA positivity, being aged 60 years, and urinary output (oligoanuria) at presentation [8]. Oligoanuria at presentation and the percentage of crescents predicted the dependence on dialysis at 3 months.…”
Section: Introductionmentioning
confidence: 98%